080 The diagnostic journey of mitochondrial disease patients. (23rd August 2021) - Rudaks, Laura I; Watson, Eloise; Lubomski, Michal; Edema-Hildebrand, Fabienne; Ahmad, Kate; Liang, Christina; Davis, Ryan; Sue, Carolyn
Abstract : Introduction: Mitochondrial disorders can often be challenging to diagnose and patients may undergo protracted investigative odysseys before reaching a diagnosis. 1 This study reviewed the diagnostic journey for genetically confirmed Mitochondrial Disease patients. Methods: Patients with a genetic diagnosis of mitochondrial disease seen at the Department of Neurogenetics, Royal North Shore Hospital, were invited to complete an online survey at their appointment or via telephone. Participant clinical records were reviewed for additional data, including genetic diagnosis. Results: Between October 2018 and April 2020, survey results were obtained from 68 patients. The most common presenting symptoms were fatigue (39%), weakness (31%), and droopy eyelids (31%). The most frequently completed investigations were MRI (55%), neurophysiologic testing (45%) and EEG (44%). 33% of participants had consulted five or more doctors with an overall mean time to diagnosis of 6.2 years. 41% of patients received a diagnosis within two years of symptom onset, 31% between 5 and 15 years, and 11% after 15 years or more. 38% of participants received at least one alternative diagnosis prior to their definitive genetic mitochondrial disease diagnosis. Following diagnosis, 34% of patients joined a support group and 87% felt that this was beneficial. Conclusions: Our results demonstrate that many patients experience long delays, undergo many investigations and see multiple doctors before a diagnosis of mitochondrial disease is reached. It is hoped that advances in diagnostic pathways and access to earlier genetic testing may streamline the process. 2 References: Grier J, Hirano M, Karaa A, et al . Diagnostic odyssey of patients with mitochondrial disease. Results of a survey. Neurol Genet 2018;4 : e230. doi:10.1212/NXG.0000000000000230 Watson E, Davis R, Sue C. New diagnostic pathways for mitochondrial disease. J Transl Genet Genom 2020;4 :188–202.